Prevalence and knowledge of carpal tunnel syndrome among the dental practitioners; survey based study in Riyadh - Anfal AlAnazi, Dr.; Lujain AlZahrani, Dr.; Heba Alshammary, Dr.; Nadeen AlMaghamsi, Dr.; Saja Alobaidi, Dr.; Shahzeb Ansari, Dr. (International Journal of Dental Research, 2019)
Carpal Tunnel Syndrome (CTS) is a common medical condition that results in numbness, pain and tingling in the arm and constitutes about 90% of neuropathy entrapments. The condition arises when the median nerve in the arm is compressed. CTS can degenerate rapidly to cause nerve damage. The effects of CTS on medical practitioners can be serious given the speculation that the condition is work-related. Consequently, this study seeks to establish the prevalence and knowledge of CTS among dental practitioners in the city of Riyadh. In doing so, the research attempts to find relationships between CTS and workload and the experience of the dental practitioners. The study takes the model of sectional study that targets dental practitioners specifically in the city of Riyadh. The researchers recruited 190 dentists and used google forms to collect data from the respondents. The questions in the survey related to symptoms of the condition and the related demographics. The study found a significant comparison of the prevalence and knowledge of CTS among various subgroups. Daily patient exposure and work experience were some of the underlying features discovered in the study. Dentists with more work experience demonstrated significant knowledge on the condition and registered an equally high prevalence of pain associated with CST. The findings of the research show a direct correlation between workload, work experience, and CST.Â Â